Kajian Yuridis Terhadap Tindakan Pencemaran Nama Baik - Aftar Akbar; Khaerul Mannan; Iswandy Rani Saputra (Jurnal Litigasi Amsir, 2023)
This study aims to find out about the application of criminal law in Decision No.219/Pid.Sus/2019/Pn.Pre and also to find out about the legal considerations of judges in imposing Decision No.219/Pid.Sus/2019/Pn.Pre. The type of research to be carried out is the normative approach method. The normative approach or commonly referred to as doctrinal research is an approach that is carried out by means of regulations reviewing literary materials such as legislation, theories, and legal principles related to the problem being tested. The application of the criminal law for defamation based on the Decision of the Parepare District Court No.219/Pid.Sus/2019/PN.Pre which states that the prosecution of the public prosecutor is unacceptable and the Defendant is immediately released from Detention is correct and appropriate based on applicable law. Furthermore, the legal considerations of the case judge No.219/Pid.Sus/2019/PN.Pre stated that the phrase in Article 319 of the Criminal Code, namely "except under Article 316" was declared contrary to the 1945 Constitution of the Republic of Indonesia and has no force. legally binding. So the consequence is that every government official or state official who feels insulted or defamed must report the offense himself. It is appropriate according to law and in line with the decision of the constitutional court No.31/PUU-XIII/2015. As a suggestion, it is hoped that investigators from the police are not in a hurry to determine someone who is being reported to be named a suspect and the prosecutor's office as a research prosecutor and at the same time acts as a public prosecutor to be careful and thorough in declaring a case to be complete and it is also hoped that the police and the Attorney General's Office to study more deeply about the application of the criminal complaint law so that in the future there will be no community members who feel disadvantaged due to an error in the application of the law and carefully consider taking measures to restrain the suspect/defendant.